Advance care planning after hospital discharge: qualitative analysis of facilitators and barriers from patient interviews - Peck, Vanessa; Valiani, Sabira; Tanuseputro, Peter; Mulpuru, Sunita; Kyeremanteng, Kwadwo; Fitzgibbon, Edward; Forster, Alan; Kobewka, Daniel (Université d'Ottawa | University of Ottawa, 2018)
Abstract Background Patients who engage in Advance Care Planning (ACP) are more likely to get care consistent with their values. We sought to determine the barriers and facilitators to ACP engagement after discharge from hospital. Methods Prior to discharge from hospital eligible patients received a standardized conversation about prognosis and ACP. Each patient was given an ACP workbook and asked to complete it over the following four weeks. We included frail elderly patients with a high risk of death admitted to general internal medicine wards at a tertiary care academic teaching hospital. Four weeks after discharge we conducted semi-structured interviews with patients. Interviews were transcribed, coded and analysed with thematic analysis. Themes were categorized according to the theoretical domains framework. Results We performed 17 interviews. All Theoretical Domain Framework components except for Social/Professional Identity and Behavioral Regulation were identified in our data. Poor knowledge about ACP and physician communication skills were barriers partially addressed by our intervention. Some patients found it difficult to discuss ACP during an acute illness. For others acute illness made ACP discussions more relevant. Uncertainty about future health motivated some participants to engage in ACP while others found that ACP discussions prevented them from living in the moment and stripped them of hope that better days were ahead. Conclusions For some patients acute illness resulting in admission to hospital can be an opportunity to engage in ACP conversations but for others ACP discussions are antithetical to the goals of hospital care.